Collaborative Research: The face of Youth and Adult Education research and the subjects implications - Freitas, Marinaide Lima de Queiroz; Ribeiro, Nadja Naira Aguiar (Education Policy Analysis Archives, 2014)
This paper, part of an ongoing longitudinal research (2012-2015), aims to reflect on the procedures of collaborative research that, by favoring spaces of learning between school and university, highlights the movements of otherness among subjects involved in research activity. Committed to the idea of making a survey of teachers of Youth and Adult Education (YAE) in the public school and not about them, this approach was elected to put focus on the teaching of reading. As theoretical and methodological support to certain categories of the discussion of this article, we sought to dialogue with Bakhtin (2003), Freire (2006, 1981, 1979), Ibiapina (2008) among others that contribute to the theme in question. The discussion sessions held, such as the episode analyzed in this work, reveals that the epistemological and methodological foundations of collaborative research, in addition to subverting the positivist model of science, contributes to the continuous education of these YAE teachers, with the school context, as well with the researchers themselves.